THE ROLE OF NATIONAL-SPIRITUAL VALUES IN FAMILY FORMATION - Саламова, Камала; Керімова, Севіндж (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
Preservation of national and aesthetic values plays an important role not only from the sociopsychological point of view, but also from the point of view of preserving the culture and traditions of the family. National traditions and customs have passed a long secular path of development. They are filed with respect for adults and youngsters, national characteristics and boundless love for a woman. All this is most clearly reflcted in family relations. The family is a structure where material relations are balanced and at the same time spiritual values are preserved for centuries. A family that is of great importance in the development of the human society is an indicator of its cultural development. The behavior of people, as you know, depends on the level of development of society. Reached to our days, manifested in the style of behavior and actions that belonged to the people of quality, i.e. the ever-living traditions and customs of our regions are of great importance for proving their deep roots. In ceremonies, including some traditions and historically formed customs, the qualities peculiar to the people with all their shades are passed from generation to generation. From the socio-psychological point of view, the preservation of national-spiritual values, a number of factors, including family culture, play a unique role. From time immemorial, passing through the «sieve» of people’s thinking, our customs and traditions, respect for father and mother, elder and younger, immense love for the woman’s personality found its strong point in the family